An human-computer interface using facial gestures for the game of Truco - Castillo, G. (2012)
In this work we present a method to detect and recognize the signs of the card game of Truco which are a subset of facial gestures. The method uses temporal templates to represent motion and later extract features. The proposed method works in real time, allowing to use it as an human-computer interface , for example, in the context of the card game of Truco . To the best of our knowledge this is the first work that uses detection of facial gestures in the context of a game. © 2012 Springer-Verlag.